Mathematical Methods in Computer Science: Essays in Memory of Thomas Beth - Hutchison, David; Kanade, Takeo; Kittler, Josef (Lecture Notes in Computer Science, 2008)
This Festschrift volume contains the proceedings of the conference Mathematical Methods in Computer Science, MMICS 2008, held December 2008, in Karlsruhe, Germany, in memory of Thomas Beth. The themes of the conference reflect his many interests.